ANALISIS POLA INTERAKSI DENGAN MENGGUNAKAN BAHASA BALIK PADA KOMUNITAS PUNK “ BEKASI VARIAL BEKASI - Yohanes Soni Sianturi; Seto Herwandito (Universitas Kristen Satya Wacana, 2014)
Bekasi Varial Punk Community is one punk community which is still exsist until now located at bekasi. This community has an unique characteristic in doin communication, because they communicate with a slighty different language which is ‘return language’. In term of their communication, ‘return language become the primary language.This research is to know how the communication pattern of Bekasi Varial Punk Community when they use ‘return language’. The methode which is used is qualitative approximation with descriptive research.The end result of this research is that Bekasi Varial Punk Community has various pattern of interaction. This pattern of interaction always be related depends on the situation and topic they being discussed. The pattern of interaction isused because rhis community adheres to the principle of unity and concensus.Key words: Communication, language, interaction pattern, community.